Feature of training of the gifted youth and becoming of the teacher - tutor in the modern Germany through a prism of pedagogical views of G.Skovoroda - Stepanets I.A (Kharkov National Pedagogical University, 2010)
Pedagogical conditions and features of educational process for the gifted youth are construed. Their correspondence to system of scientific views of G.Skovoroda is exhibited. Their likeness to G.Skovoroda pedagogical ideas is installed. Views on the nature of special capabilities for the person, requirement of their development for activity, necessity of the professional education for capable pupils, demands to the teacher - tutor are stressed. Necessity of special training and the special approach to education of the gifted personality is scored.